Women on Board on Companies Performances and Fraud Tendencies: Evidence from Indonesia’s Energy Industry - Agoestina Mappadang; Winnie Bernadine (Universitas Muhammadiyah Malang, 2024)
Purpose: This research examines how the presence of women on company boards affects financial performance, stock performance, and the detection of financial statement manipulation. Methodology/approach: Using a purposive sample method of data from 54 energy sector companies listed on the Indonesia Stock Exchange from 2018 to 2022, this research exerts panel regression analysis using EViews 9. Findings: The research results show that a female board of commissioners has a significant impact on financial performance and detection of financial report manipulation, but not stock performance. In addition, financial performance variables can mediate the relationship between women on board and detection of financial statement manipulation. Practical and Theoretical contribution/Originality: Previous research has largely been limited to exploring the correlation between gender diversity and firm performance, as well as manipulation, separately. Research Limitation: The sector is affected by global economic trends and natural factors, causing inefficiencies in the capital market and investor reactions to internal company data.